Some control problems for simplest differential models of proliferation cycle - Świerniak, Andrzej (1950- ) (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents probably the simplest models of chemotherapy considered as a control problem. The first-order tumour growth kinetic models both of Malthusian and Gompertzian type are discussed, and their "degenerated" control properties are indicated.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka